Stereoselective construction of 5,11-methanomorphanthridine and 5,10b-phenanthridine structural frameworks: total syntheses of (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine - Pandey, Ganesh; Gadre, Smita R. (Pure and Applied Chemistry, 2012)
The core structure of the complex pentacyclic 5,11-methanomorphanthridine skeleton and the vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton are constructed stereospecifically in one step employing intramolecular 1,3-dipolar cyclo addition of a nonstabilized azomethine ylide (AMY) generated by the sequential double desilylation of appropriate bis-trimethylsilylmethyl amines using Ag(I)F as a single-electron oxidant. The strategy is successfully applied for the total synthesis of biologically active alkaloids such as (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine.
Keywords: alkaloid synthesis; cycloadditions; organic synthesis; stereocontrolled synthesis